Efektivitas Pelatihan Perencanaan Karir Untuk Meningkatkan Kejelasan Arah Pilihan Bidang Minat Karir Pada Mahasiswa Semester III Fakultas Psikologi - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
ABSTRACT The research aims to examine the effectiveness of career planning in making a firm career choice of the third semester of psychology stUdents. The research was conducted 'experimentally using the pre test post test group design. The measurements were based on a scale which were carried out three times on the subjects, i.e. at the pre test, the post test-1 (after training), and the post test-2 (two weeks after the measurement). Furthermore, a qualitative analysis was done derived from the FGD (Focus Group Discussion) results and the career information forms distributed at the pre test, the training evaluation, and the observation during the training at the post test 1, and the in-depth interview during the post test-2. The subjects of this study were 44 students of Faculty of Psychology, Ahmad DahIan University, Yogyakarta, which were splitted into a control group (22 students) and a experimental group (22 students). The results show that: (1) there is a very significant difference in choice of career intention of the experimental group observed in the pre test, the post. test-1, and the post test-2 (F = 109,320, p < 0,05), (2) there is a very significant difference in choice of career intention of the experimental group observed in the pre test, the post test 1(t = -6.263 dan p < 0.01, X pre test = 157.05, andpost test-1 = 172.05), (3) there is a very significant difference in choice of career intention of the experimental group observed in the post test-1, the post test-2 (t = -9.557 dan p < 0,01, post test-1 = 172.05 dan post test-2 = 174), (4) there is a very significant difference between the experimental group dan the control group in the gained score-1 (z = -5.693, p < 0.01, gained score-1 of the experimental group = 15.45, gained score-1 of the control group = 0.36), (5) there is